Epididymal Cysts: Are They Associated With Infertility?. Issue 3 (May 2018) - Weatherly, David; Wise, Phil G.; Mendoca, Shawn; Loeb, Aram; Cheng, Younjun; Chen, John J.; Steinhardt, George
Scrotal sonography is commonly used for evaluation of the infertile male. While epididymal cysts are frequently observed during sonographic assessment, their presence has uncertain import. This study is a retrospective case-control sonographic and chart review comparison of infertile men and fertile volunteers to clarify the possible association of epididymal cysts and infertility. The study included 91 consecutively recruited patients from January 2012 to December 2014. The infertile group consisted patients with male factor infertility who underwent scrotal sonography ( n = 67). The fertile group consisted of men requesting vasectomy who were recruited for study involvement and consented to undergo scrotal sonography ( n = 24). The main outcome measure was infertility. The existence of epididymal cysts on scrotal sonography was the main risk factor. Predictably, the only sonographic findings associated with infertility were small testes (right: t (df = 89) = −2.52; left: t (df = 89) = −2.28, both p = .01) and the presence of a varicocele, χ 2 (df = 1) = 5.766 with p = .02. The infertile men were also younger and more likely to use alcohol. Of the 91 men studied, 71% demonstrated epididymal cysts (73% of infertile and 67% of fertile men). Epididymal cysts were not be associated with infertility, χ 2 (df = 1) = 0.362 with p = .55. This occurrence of epididymal cysts is the highest ever reported (71% of all men). While the occurrence of epididymal cysts in this cohort is unexplained, our observation that these cysts are not associated with infertility will be useful for those clinicians counseling patients observed to have these structures.